ASSOCIAÇÃO ENTRE COMPORTAMENTOS DE RISCO PARA DESENVOLVIMENTO DE TRANSTORNO ALIMENTAR E DESEMPENHO FÍSICO EM ATLETAS: UM ESTUDO TRANSVERSAL - Adolfo Henrique Costa dos Santos (2022)
Introduction: Among the most prevalent eating disorders (ED) are Anorexia Nervosa (AN), Bulimia Nervosa (BN) and the Binge Eating Disorder (BED). The etiology of ED is considered multifactorial, and implies psychosocial losses, impairment concerning physical health, and complications for sports practice. However, there is little evidence in the literature showing variations and implications between the risk of ED development and physical performance, whether in amateur or professional athletes. Objective: Assess the correlation between risk behaviors for ED and physical performance in Brazilian athletes. Methods: This is a cross-sectional study with a non-probabilistic sample, composed of federated athletes of several sports, of both genders, aged 12 to 41 years, from the Medal Project (Multiprofessionalism in Sports: Determinants of High Performance and Longevity of Athletes) between 2013 and 2019. The screening for risk of developing ED was done by means of the Eating Attitudes Test (EAT-26) instrument. The physical performance assessed by means of the Running Anaerobic Sprint Test - RAST, Vertical Jump - VJ and the Yo-yo Test. Anthropometric evaluation included body mass and height. The findings of the study were obtained by measures of central tendency, dispersion, and frequencies. The comparison of the athletes' physical performance with the risk for ED was made based on the Multiple Linear Regression Analysis, and to describe the further study variables, the IBM SPSS version 24 statistical program was used, and the Chi-square test and the Shapiro-Wilk test were carried out, with the adopted significance levels being 5% (p < 0.05). Results: The results of the 329 athletes participating in the research pointed to a sample composed of 74.16% male and 25.84% female with a mean age of 23.66 ± 2.87 years (12 to 41 years-old), drawn from 20 different sports. In the herein study, the risk for ED was higher among males (7.38%) in comparison to females (4.71%) and among practitioners of individual sports (11.45%) when compared to team sports (3.54%). Conclusions: The degree of affectedness found for ED risk behavior was considered higher among male athletes and in athletes of individual sports. The values referring to ED were considered non-significant and did not present any correlation with the performance variation of the athletes, i.e., it was not possible to verify a decrease in the performance of the athletes who took part in this study.